APLIKASI METODE GAYA BERAT UNTUK INDENTIFIKASI POTENSI HIDROKARBON DI DALAM CEKUNGAN JAKARTA DAN SEKITARNYA - Panjaitan, Saultan (Pusat Survei Geologi, 2009)
Bouguer anomaly in Jakarta Basin can be grouped into 2 parts there are the Bouguer anomaly of 40 mgal to 60 mgal showing limestone and volcanic breccia. Bouguer anomalies 20 mgal to 40 mgal indicate sedimentary rock basin. Rock units based on residual anomaly are grouped into 6 parts: Kaliwangu Formation or Cisubuh Formation with a density of 2.5 gr /cm3, Subang Formation with a density of 2.45 gr / cm3, Parigi Formation / Cibulakan with a density of 2.7 gr / cm3, Jatiluhur Formation with a density of 2. 6 gr / cm3, Jatibarang Formation 2.8 gr/cm3, metamorphic bed rocks / intrusive rocks with a density of 2.9 gr /cm3, Rengasdengklok and Karawang anticline are interpreted as a good prospective hydrocarbon formed in a residual anomaly of 10 mgal with a density 2.7 gr / cm3 depthness between. 1900-2200m. Jakarta anticline to the south and Bekasi anticline are interpreted as having the prospect with residual anomalies of 0-4 mgal, but having a smaller dimension. Lower Cibulakan Formation is as the source rock consisting of shale lacustrine, and the reservoir rocks are Cibulakan and Parigi Formation with the thickness of + 400 m consisting of limestone cavities. Pretertiary bedrock with the density of 2.9 gr/ cm3 consists of metamorphic / igneous rocks . Keywords: gravity, residual anomaly, formation, anticline, oil and gas